2015
DOI: 10.1007/s10495-015-1128-y
|View full text |Cite
|
Sign up to set email alerts
|

Fructose induces mitochondrial dysfunction and triggers apoptosis in skeletal muscle cells by provoking oxidative stress

Abstract: Mitochondrial dysfunction in skeletal muscle has been implicated in the development of insulin resistance, a major characteristic of type 2 diabetes. There is evidence that oxidative stress results from the increased production of reactive oxygen species and reactive nitrogen species leads to mitochondrial dysfunction, tissue damage, insulin resistance, and other complications observed in type 2 diabetes. It has been suggested that intake of high fructose contributes to insulin resistance and other metabolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 56 publications
4
57
2
Order By: Relevance
“…The damage to hepatic mitochondrial integrity and mtDNA repair and replication mechanisms due to the fructose-rich diet could therefore lead to liver dysfunction, and consequently to metabolic diseases. Interestingly, it has been recently shown that exposure of skeletal muscle cells to fructose elicited damage similar to that found here by us in the liver, namely it increased oxidative stress and mitochondrial dysfunction, as well as decreased mitochondrial DNA content [37]. In contrast, Yamazaki et al [38] found increased mitochondrial gene expression and mtDNA content in the liver of rats fed with fructose-containing drinking water.…”
Section: Discussionsupporting
confidence: 67%
“…The damage to hepatic mitochondrial integrity and mtDNA repair and replication mechanisms due to the fructose-rich diet could therefore lead to liver dysfunction, and consequently to metabolic diseases. Interestingly, it has been recently shown that exposure of skeletal muscle cells to fructose elicited damage similar to that found here by us in the liver, namely it increased oxidative stress and mitochondrial dysfunction, as well as decreased mitochondrial DNA content [37]. In contrast, Yamazaki et al [38] found increased mitochondrial gene expression and mtDNA content in the liver of rats fed with fructose-containing drinking water.…”
Section: Discussionsupporting
confidence: 67%
“…Fructose-induced ER stress activation has been linked to the activation of SREBP-1c, associated with the upregulation of lipogenic enzymes genes, with downstream effect on insulin sensitivity 92,119 . High-fructose or sucrose diet can also results in CHOP upregulation and JNK activation 120,121 , which further induce cellular apoptosis subsequent to BH3-only proteins BIM and PUMA-mediated mitochondrial dysfunction and caspase 3 activation 122 and glucose can further amplify FA-induced ER stress 123 (Table 1). …”
Section: ) Harmful Effects Of Hepatotoxic Carbohydratesmentioning
confidence: 99%
“…In different tissues of fructose-fed animals, mitochondrial dysfunction is detected, characterized by increased mitochondrial mass [62,63], decreased mitochondrial electron transport capacity [62,63], loss of mitochondrial membrane potential [64] and disturbance of antioxidant defense [32]. In turn, insulin resistance affects FFA-mediated mitochondrial uncoupling [65].…”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%